Fundamentals of financial accounting - Phillips, Fred , 1918-; Libby, Patricia A.; Libby, Robert (McGraw-Hill Irwin, 2011)
Presents an analysis of the fundamentals of financial accounting. This title also presents a study of both the accounting activities that take place inside the company, as well as evaluating their impact on decisions, and users outside the company. It provides the tools for students to grasp financial accounting from the ground up